Mechanism, kinetics and microbiology of inhibition caused by long-chain fatty acids in anaerobic digestion of algal biomass. Issue 1 (December 2015) - Ma, Jingwei; Zhao, Quan-Bao; Laurens, Lieve; Jarvis, Eric; Nagle, Nick; Chen, Shulin; Frear, Craig
Abstract Background Oleaginous microalgae contain a high level of lipids, which can be extracted and converted to biofuel. The lipid-extracted residue can then be further utilized through anaerobic digestion to produce biogas. However, long-chain fatty acids (LCFAs) have been identified as the main inhibitory factor on microbial activity of anaerobic consortium. In this study, the mechanism of LCFA inhibition on anaerobic digestion of whole and lipid-extracted algal biomass was investigated with a range of calcium concentrations against various inoculum to substrate ratios as a means to alleviate the LCFA inhibition. Results Whole algal biomass ofNannochloropsis salina represents high lipid content algal biomass while lipid-extracted residue represents its low lipid counterpart. The anaerobic digestion experiments were conducted in a series of serum bottles at 35 °C for 20 days. A kinetic model, considering LCFA inhibition on hydrolysis, acidogenesis as well as methanogenesis steps, was developed from the observed phenomenon of inhibition factors as a function of the LCFA concentration and specific biomass content or calcium concentration. The results showed that inoculum to substrate ratio had a stronger effect on biogas production than calcium, and calcium had no effect on biogas production when inoculum concentration was extremely low. The microbial community analysis by high-throughput Illumina Miseq sequencing indicated that diversity of both bacterial and methanogenic communities decreased with elevation of lipid concentration. Hydrolytic bacteria and aceticlastic methanogens dominated bacterial and archaea communities, respectively, in both high and low LCFA concentration digesters. Conclusions This study demonstrated that inoculum concentration has a more significant effect on alleviating LCFA inhibition than calcium concentration, while calcium only played a role when inoculum concentration met a threshold level. The model revealed that each functional microbial group was subject to different levels of LCFA inhibition. Although methanogens were the most susceptible microbes to LCFA inhibition, the inhibition factor for hydrolytic bacteria was more highly affected by inoculum concentration. The microbial community analysis indicated that the bacterial community was affected more than the methanogenic community by high LCFAs concentration. Syntrophic acetogens were sensitive to high LCFA concentrations and thus showed a decreased abundance in such an environment.Graphical abstract Proposed mechanism of calcium mitigated LCFA inhibition